2021
DOI: 10.1021/acs.jafc.1c02018
|View full text |Cite
|
Sign up to set email alerts
|

Caged Phytohormones: From Chemical Inactivation to Controlled Physiological Response

Abstract: Plant hormones, also called phytohormones, are small signaling molecules regulating a wide range of growth and developmental processes. These unique compounds respond to both external (light, temperature, water, nutrition, or pathogen attack) and internal factors (e.g., age) and mediate signal transduction leading to gene expression with the aim of allowing plants to adapt to constantly changing environmental conditions. Within the regulation of biological processes, individual groups of phytohormones act most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Moreover, there is still much missing information and gaps in the understanding of the interactions between cGMP and hormones in response to pathogen infection. There is evidence that cGMP, GCs [ 4 , 5 , 14 ], and hormones are involved in the plant response to pathogen infection [ 15 , 16 , 17 , 18 ]. Therefore, it is worth exploring whether and how these molecules cooperate.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is still much missing information and gaps in the understanding of the interactions between cGMP and hormones in response to pathogen infection. There is evidence that cGMP, GCs [ 4 , 5 , 14 ], and hormones are involved in the plant response to pathogen infection [ 15 , 16 , 17 , 18 ]. Therefore, it is worth exploring whether and how these molecules cooperate.…”
Section: Introductionmentioning
confidence: 99%
“…Silica gel was used for flash column chromatography. The 1 H and 13 C spectra were recorded in CDCl 3 using Bruker spectrometers at 500 and 125 MHz, respectively. The UV/vis absorption spectra were recorded on a Persee UV−vis spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Although various articles and reviews related to caged PGRs have been reported, 15,16,36−39 most of them focused on the strategy of using PRPGs as "switches" to trigger biological activity release. In this report, to potentiate bioefficacy and costeffectiveness, a series of caged DHGA 5 derivatives were designed 13 Caged compounds are metabolically inert after being applied to the biological system, while light exposure leads to the release of active molecules that trigger the expected physiological response. based on o-nitrobenzyl (oNB), and phototriggered active DHGA 5 release could be achieved through ester bond cleavage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations